Reducing Resource Consumption. A Proposal for Global Environmental Policy. - Bernd Meyer (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2008)
The world has just recognized that market failures of the global financial system have the power to destroy the entire economy. Short term profit maximization and wrong prices of the products are the problematic factors. Even the CEO`s of leading financial institutions demand a framework of rules that is able to avoid for the future what just has happened. The same reasons are responsible for the destruction of nature as a result of the economic process and insofar there is a window of opportunity for a general structural change in global policy. But the analogy is not perfect because the environmental problem is a long run problem and the coming catastrophe is not seen by everyone. Further many of those who are convinced that we have to act now see several distinct problems that are identified as externalities of the economic process and do not accept that we have a systematic problem. The paper at hand addresses this conflict and asks for a pragmatic policy proposal that will be able to induce a more sustainable economic development.
Keywords: Q43; O11; Q58; 330; Consumption; Global Environmental Policy